ANALISIS DAERAH POTENSI PERSEBARAN DEMAM BERDARAH DENGUE DI DKI JAKARTA DENGAN MENGGUNAKAN METODE CLUSTERING K-MEANS - Hani Dzikra Nurkhairiyyah (2022)
Dengue Hemorrhagic Fever is one of the infectious diseases in Indonesia. Dengue fever is caused by the bite of Aedes aegypti and Aedes albopictus mosquitoes. This study aims to cluster the potential areas for the distribution of DHF in DKI Jakarta. Clustering is done using the K-Means algorithm, by determining the number of k clusters to be divided. The data used is the result of data design by combining several attributes. The value of K is determined through the results of the Silhouette evaluation by calculating the Silhouette Score. The resulting Silhouette Score is 0.41642 at K=2, so it was decided to divide the data into 2 clusters. The clustering results consist of C0 is a sporadic area, include 30 sub-districts, namely Cempaka Putih, Gambir, Johar Baru, Kemayoran, Menteng, Sawah Besar, Senen, Tanah Abang, Kelapa Gading, Koja, Pademangan, Tanjung Priok, Grogol Petamburan, Palmerah, Taman Sari, Tambora, Cilandak, Jagakarsa, Kebayoran Baru, Kebayoran Lama, Mampang Prapatan, Pancoran, Pesanggrahan, Setiabudi, Tebet, Matraman, Pasar Rebo, Pulo Gadung, Kepulauan Seribu Selatan, dan Kepulauan Seribu Utara. C1 endemic area, consists of 14 sub-districts, which is Cilincing, Penjaringan, Cengkareng, Kalideres, Kebon Jeruk, Kembangan, Pasar Minggu, Cakung, Cipayung, Ciracas, Duren Sawit, Jatinegara, Kramat Jati, and Makasar.